Tuning the performance of low-Pt polymer electrolyte membrane fuel cell electrodes derived from Fe2O3@Pt/C core-shell catalyst prepared by an in situ anchoring strategy - Dhavale, Vishal M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2012)
A low-Pt electrode with high performance and durability characteristic has been realized for polymer electrolyte membrane fuel cell applications from a carbon-supported Fe2O3@Pt core-shell catalyst prepared by a process involving in situ surface modification-cum-anchoring strategy. The process is based on an in-house-developed methodology for generating and interlocking the core-shell nanoparticles on the surface of the carbon substrate, which undergoes functionalization in the reaction medium itself by the intervention of the reducing agent employed in the reaction. Ascorbic acid, which was used as the reducing agent in the process, played a crucial role by making use of its multifunctional activities as reducing agent, stabilizing agent, as well as capping agent in addition to its efficiency in functionalizing the carbon surface during the course of the reaction. The formation of core-shell nanostructures could be confirmed by XRD, HR-TEM, and cyclic voltammetric analysis. The oxygen reduction property and the performance during the single cell evaluations were found to be strongly influenced by the thickness of the catalyst layer owing to the ohmic contribution from the higher mass fraction of the less conductive Fe2O3 core. However, when the thickness of the catalyst layer was kept within the threshold level, Fe2O3@Pt catalyst clearly outperforms the commercial Pt/C catalyst. This benefit of the core-shell catalyst enabled it to display a maximum power density of 900 mW/cm(2) with a significantly low cathode Pt loading of 0.05 mg/cm(2). An accelerated durability assessment of the membrane electrode assembly for 10 h gave consistent performance characteristics. The study gave convincing evidence on the feasibility of using the electrodes derived from the core-shell catalyst prepared by the in situ anchoring strategy for developing cost competitive systems and miniature cells for niche applications.